PELAKSANAAN SUPREVISI AKADEMIK PENGAWAS PADA KOMPOTENSI DAN PROFESIONALISME GURU IPS TERPADU DI SMP KECAMATAN TAYANDO TAM KOTA TUAL PROPINSI MALUKU - Rahanantan, Haruna; Salamah (Jurnal Sosialita, 2024)
This study aims to identify and describe the objective condition of academic supervision practices by school supervisors, the professional competence of Integrated Social Studies (IPS) teachers, and the supporting and inhibiting factors affecting academic supervision implementation at junior high schools in Tayando District, Tual City, during the 2023/2024 academic year, along with proposed solutions. This qualitative research involved seven participants, including three principals, three IPS teachers, and one supervisor. Data were collected through interviews, observations, and documentation, while data validity was ensured through source triangulation. The data were analyzed descriptively and deductively using a naturalistic approach. The findings indicate that the implementation of academic supervision by supervisors in Tayando Tam District public junior high schools remains suboptimal. Supervisors’ visits tend to be brief and infrequent, limiting the effectiveness of teacher guidance. The professional competence of IPS teachers varies in mastery of subject matter, understanding of core and basic competencies, development of teaching materials, and utilization of information technology—some teachers perform well, while others are still moderate. Supporting factors include supervisor accreditation and welfare, while inhibiting factors involve low motivation among teachers and principals, insufficient supervisor qualifications and competencies, uneven distribution of supervisors, and inadequate school facilities and infrastructure.